Mill and pave road and related work at Dahlia Street, Bandar Baru Salak Tinggi for Majlis Perbandaran Sepang / Fakhri Arif Mohd Jamil - Mohd Jamil, Fakhri Arif (Universiti Teknologi Mara, Perak, 2016)
KSB Global Sdn. Bhd. A construction company registered with Minister of Finance. General contractor, construction , M&E and other related jobs. Established in January 2008 as a Bumiputera Status Company with a reasonable track records of qualified and experienced management and technical team related to the above fields. 9 years experienced in this construction and maintenance field KSB Global Sdn Bhd also was build up from 2 siblings which is qualified from UniKL & UiTM. KSB Global Sdn Bhd located 11km from KLIA Airport and 13km from Sepang International Circuit. Provide a top priority commitment towards our valued customers’ satisfaction with a competitive quality services and offers.